Peran Company Growth dalam Memoderasi Hubungan Audit Report Lag dan Kepemilikan Publik Terhadap Auditor Switching - Fiska Nurul Aini Siregar; Suciati Muanifah (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
Auditor switching is very important for companies because it maintains the independence of auditors and has objectivity in assessing the fairness of the company's financial statements and maintaining public trust. This study aims to determine the role of company growth in moderating the relationship between audit report lag and public ownership to auditor switching. This research was conducted using quantitative methods and the data source used, namely secondary data taken from the Indonesia Stock Exchange in the form of annual financial statements. The population in this study is 70 companies in the infrastructure sector in 2019 – 2023. The sampling technique used is purposive sampling. The sample in this study is 21 companies with a total of 105 sample data. The data analysis technique used in this study is logistics regression using the Eviews version 12 application. The results of this study show that simultaneously Audit Report Lag and Public Ownership have an effect on Auditor Switching. While partially Audit Report Lag has no effect on Auditor Switching, Public Ownership has no influence on Auditor Switching. The role of Company Growth is able to moderate the relationship between Audit Report Lag and Auditor Switching. The role of Company Growth is not able to moderate the relationship between Public Ownership and Auditor Switching.